Enhancing the capacity for optimal social and personality function through the mediational intervention for sensitizing caregivers: A case illustration. Issue 5 (17th May 2021) - Sharp, Carla
Abstract: Objective : Based on the well‐known principle that the ability to meaningfully relate to others starts in the context of early attachment relationships, the current case illustration uses a recent extension of mentalization‐based theory and practice to demonstrate how caregivers can enhance the capacity for optimal social and personality function through the mediational intervention for sensitizing caregivers (MISC). Methods : Case material is presented to demonstrate the implementation of the MISC affective and cognitive components with a mother of an adopted 10‐year‐old girl who shows signs of affect avoidance, social isolation within and outside the family, and maladaptive personality development. Results : The case illustration shows how video feedback sessions facilitate the gradual use of affective and cognitive components in the daily interactions between mother and daughter, thereby scaffolding optimal social and personality development. Conclusions : Affective and cognitive components of the Mediational Intervention for Sensitizing Caregiving can be effectively integrated to enhance mentalizing capacity in caregiver‐child interactions.